Living yam poles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The production of poles for yam culture is labour intensive, costly and difficult to mechanize. Furthermore, suitable bush sticks cannot always be obtained locally. These difficulties can be overcome by growing suitable trees in the field. In the...